Generation Z Students’ Responses to the Collaboration of Conventional and Modern Learning Media in Islamic Religious Education - Saputra, Adi; Mahmud, Salami; Bayani, Nur (DAYAH: Journal of Islamic Education, 2026)
This study examines Generation Z students’ responses to the collaboration of conventional and modern learning media in Islamic Religious Education (PAI). A mixed-methods approach was employed using a seven-item Likert-scale questionnaire complemented by open-ended questions. Data were collected from 52 senior secondary students in Aceh Province through student-level random sampling. Quantitative data were analyzed descriptively using frequencies and percentages, while qualitative responses were interpreted through thematic analysis. The findings indicate that conventional learning media remain positively perceived because they support clearer understanding of PAI content, strengthen focus and discipline, and facilitate value internalization through direct classroom interaction. At the same time, modern learning media—particularly video-based resources and interactive applications—are perceived to enhance engagement, accessibility, and learning motivation. Qualitative evidence further suggests that students view the integration of both media types as complementary: conventional approaches provide structure, seriousness, and moral guidance, whereas modern media enrich learning through variety, interactivity, and flexibility. These results underline the importance of an integrative PAI learning strategy that remains value-oriented while responding to Generation Z learning preferences in the digital era.